2023
DOI: 10.1186/s12931-023-02493-4
|View full text |Cite
|
Sign up to set email alerts
|

Chronic intermittent hypoxia increases airway hyperresponsiveness during house dust mites exposures in rats

Abstract: Introduction Accumulating clinical evidence links Obstructive Sleep Apnea (OSA) with worse outcomes of asthma, but impact on airway function remains sparsely studied. We tested effects of Chronic Intermittent Hypoxia (CIH) – a hallmark of OSA – on airway hyperresponsiveness (AHR), in a rat model of chronic allergen-induced inflammation. Methods Brown Norway rats were exposed to six weeks of CIH or normoxia (NORM) concurrent with weekly house dust m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Third, OSA is caused by respiratory abnormalities, whereas the model in the present study was induced by exposure to reduced oxygen concentrations. Although the OSA modelling based on chronic intermittent hypoxia has been widely used in multiple studies 41 43 , a suitable model for OSA is needed to verify the significance of the TCONS_00039830/miR-455-3p/ Smad2 axis in OSA and MASLD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, OSA is caused by respiratory abnormalities, whereas the model in the present study was induced by exposure to reduced oxygen concentrations. Although the OSA modelling based on chronic intermittent hypoxia has been widely used in multiple studies 41 43 , a suitable model for OSA is needed to verify the significance of the TCONS_00039830/miR-455-3p/ Smad2 axis in OSA and MASLD.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic intermittent hypoxia (CIH) was used to construct an OSA model in this study. The induction principle of OSA-related diseases including MASLD was caused by chronic hypoxia caused by OSA 41 43 . OSA could directly cause a decrease in oxygen inhalation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, chronic intermittent hypoxia (CIH) was used to construct an OSA model. The induction principle of OSA-related diseases, including metabolic dysfunction-associated steatotic liver disease, was based on OSA-induced chronic hypoxia [ 21 23 ]. OSA could decrease O 2 inhalation directly.…”
Section: Methodsmentioning
confidence: 99%
“…In sheep, bronchial responsiveness to methacholine was increased by hypoxia and the response was mediated by carotid body chemoreceptors [90]. Teodorescu and colleagues showed that chronic intermittent hypoxia increased airway hyperresponsiveness to methacholine challenge in rats exposed to house dust mites and intermittent hypoxia [91]. Intermittent hypoxia for 6 h/d for 14 days increased methacholine-induced airway hyperresponsiveness and inflammatory marks in bronchoalveolar fluid in rats [92].…”
Section: Hypoxemiamentioning
confidence: 99%